Contemporary Turkey at a Glance II : Turkey Transformed? Power, History, Culture - Ersoy, Meltem; Ozyurek, Esra (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
This volume is a collection of papers that address multiple issues of contemporary Turkish politics, presented at the "Contemporary Turkey at a Glance: Turkey Transformed? Power, History, Culture" conference. Articles on foreign policy analyze the impact of the changing dynamics in the region following the Arab Uprisings. The pressing issues of the role of the strong one party government on the transformation of political institutions and the relations between the state and the citizens, and whether there is a trend towards authoritarianism are debated. The wide range of issues extends to the formation of identity in the transnational communities, the projection of historical events, the challenges to the legal system, and last but not the least, the established categories of religion and gender. Content Turkey - Politics - History - Culture The editors Dr. Meltem Ersoy received her Political Science PhD from George Mason University. Her research focuses on political parties, political Islam and Turkey. Dr. Esra Ozyurek is the Chair for Contemporary Turkish Studies, European Institute, London School of Economics. She is a social anthropologist and she wrote books on religion and politics in Turkey and Germany.
Keywords: Social sciences.; Ethnology.; Social structure.; Social inequality.; Religion and culture.; Political sociology.; elektronické knihy; electronic books